APLIKASI PUPUK ORGANIK DAN Trichoderma sp TERHADAP HASIL TANAMAN KENTANG (Solanum tuberosum L.) DI DATARAN TINGGI - Laurensius Lehar; Maria Klara Salli; Heny M.C. Sine (Universitas Islam Kadiri, 2018)
Ndua Ria Village in the District of Kelimutu Flores is located in a highlands and is one of a central production of vegetables. The cultivation of the potato in the highlands is not optimal; it is because of the farmers which are not able to meet the needs of production facilities, such as potato seeds, fertilizer, insecticide and water in the dry season. Fertilizers and insecticides are too expensive, due to Indonesia's economy which is uncertain it gives the impact on the inability of farmers' purchasing power so that many farmers cannot grow potatoes. In an effort to reducing production costs, especially fertilizer and insecticides in this study it will be tested four kinds of organic fertilizers and trichoderma sp. The research objective is to get the type of organic fertilizer which is capable of interacting with Trichoderma sp in the control Phythopthora infestans, Yellow cyst nematode (PCN) as well as inorganic fungicide, thereby reducing production costs and get the right kind of organic fertilizer and inexpensive but provide optimal is very important. The results showed that organic fertilizer of chicken manure is able to interact with trichoderma, sp in controlling phythopthora infestans and PCN so that it can provide the optimum results against potato yield components, the grade of (6,35), weights (9,50) kg, grade of 10-30g (126.67) g, for grade 30-60 g (236.67) g and grade of > 60g (1422.67) g. For the growth and yield of potato in the plateau area it is recommended to give the optimal use of chicken manure and Trichoderma sp.